Queering Reproductive Time: Jacob’s Wrestling and Queer Temporalities in Sheila Heti’s Motherhood - Frankel, Alexandra Vieux (Canadian Jewish Studies / Études juives canadiennes, 2023)
In her book Motherhood, Sheila Heti transforms her titular subject into a state of wrestling. She divorces motherhood from biological reproduction and expands it. The result is a version of motherhood oriented toward the past rather than reproductive futures. This article argues that Heti relies on queer tropes and the biblical story of Jacob wrestling to accomplish motherhood’s transvaluation. Those tropes reproduce the antisocial theory of queerness popularized by Lee Edelman and position queerness as antithetical to reproductive futures. Jacob’s wrestling, associated with the naming of a patriarch and Jewish futures, becomes a space for interrogating conventional definitions of motherhood. The concept’s resignification contributes to current debates around Jewish continuity in North America by offering a more inclusive view of motherhood. This article shows how Heti’s work draws attention to heteronormative foundations of continuity discourses and the question of recognizing queer futures.